The Effect of Transformational Leadership Style and Work Productivity on Employee Performance in The Mediation of Job Satisfaction - Rohmaniah, Rita; Amsar, Amsar; Ikut, Camilus Isidorus (Faculty of Economics and Business UNTAG Semarang, 2025)
This study aims to analyze the influence of transformational leadership style and work productivity on employee performance with job satisfaction as a mediating variable. The research sample consisted of 110 employees selected using the proportional sampling method. Data collection was carried out through a questionnaire with a Likert scale of 1-5, and data analysis used Structural Equation Modeling-Partial Least Square (SEM-PLS). The results of the study indicate that both transformational leadership style and work productivity have a positive and significant effect on employee performance. Furthermore, both of these factors also significantly increase job satisfaction. Job satisfaction itself plays a dual role: it directly improves employee performance and acts as a mediator. The result means that transformational leadership and high productivity don't just help performance directly; they also boost performance indirectly by making employees more satisfied with their roles.